2021
DOI: 10.1099/jgv.0.001668
|View full text |Cite
|
Sign up to set email alerts
|

HERC5 E3 ligase mediates ISGylation of hepatitis B virus X protein to promote viral replication

Abstract: Ubiquitin and ubiquitin-like protein modification play important roles in modulating the functions of viral proteins in many viruses. Here we demonstrate that hepatitis B virus (HBV) X protein (HBx) is modified by ISG15, which is a type I IFN-inducible, ubiquitin-like protein; this modification is called ISGylation. Immunoblot analyses revealed that HBx proteins derived from four different HBV genotypes accepted ISGylation in cultured cells. Site-directed mutagenesis revealed that three lysine residues (K91, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Among the IFN-related differentially expressed genes, the upregulation of the ISG15 pathway is particularly remarkable. Earlier investigations into the role of ISG15 in HBV infection mostly suggested a proviral role although these were often overexpression studies 51–53 . Consequently, a specific antiviral role for the ISG15 pathway in the context of CAM-A treatment cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the IFN-related differentially expressed genes, the upregulation of the ISG15 pathway is particularly remarkable. Earlier investigations into the role of ISG15 in HBV infection mostly suggested a proviral role although these were often overexpression studies 51–53 . Consequently, a specific antiviral role for the ISG15 pathway in the context of CAM-A treatment cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier investigations into the role of ISG15 in HBV infection mostly suggested a proviral role although these were often overexpression studies. [51][52][53] Consequently, a specific antiviral role for the ISG15 pathway in the context of CAM-A treatment cannot be excluded. Interestingly, Lucifora et al [54] identified upregulation of ISG15 and other factors in the ISG15 pathway (ISG15, UBE2L6, USP18, and HERC5) when inducing high HBV replication in HepaRG cells through a baculovirus-HBV system, which was associated with an antiviral state.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that NQO1 could regulate the proteasomal degradation of HBx, thereby inhibiting HBV cccDNA activity [ 17 ]. Other studies have reported that intracellular restriction genes, including TRIM21, ISG15, and TRIM31, could eliminate HBx [ 18 , 19 , 20 ]. Another inhibition strategy against HBx could include short hairpin RNAs against HBx [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…impact of ISG15 conjugation or binding to viral factors to inhibit infection has been extensively reviewed elsewhere [36][37][38], which points toward its antiviral nature. Interestingly, more recent studies have also revealed a pro-viral function of ISG15 in replication of Hepatitis B [39] and C viruses [40]. These anecdotal reports indicate that co-evolution of viruses with their host may have enabled these pathogens to exploit ISGylation to their own benefit.…”
Section: Direct Impact Of Isg15 On Virus Replication and Spreadmentioning
confidence: 99%